HUBUNGAN TINGKAT KEPARAHAN MALOKLUSI DENGAN STATUS KARIES PADA SUKU BANJAR - Diva Nurkhaliana; Diana Wibowo; Aulia Azizah; Isnur Hatta; Patricia Iskandar (Universitas Lambung Mangkurat, 2026)
Background: Dental caries and malocclusion remain common oral health problems among school-aged children. Irregular tooth arrangement may hinder effective oral hygiene practices, resulting in greater plaque retention and an increased likelihood of dental caries. However, evidence regarding the association between these two conditions in Banjar ethnic children is still limited. Objective: To determine the relationship between the severity of malocclusion and caries status among Banjar ethnic students aged 11–12 years at SDN Sungai Andai 4, Banjarmasin City. Methods: An observational analytic study with a cross-sectional design was conducted involving 45 students selected through purposive sampling. Malocclusion severity was assessed using the Dental Health Component (DHC) of the Index of Orthodontic Treatment Need (IOTN), while caries status was evaluated using the Decayed, Missing, and Filled Teeth (DMF-T) index. The association between the variables was analyzed using Spearman’s rank correlation test. Results: The most frequently observed level of malocclusion severity was IOTN-DHC Grade 2, identified in 16 participants (35.6%). Displacement was the predominant malocclusion component, occurring in 28 cases (62.2%). The population DMF-T score was 0.69, indicating a very low caries category. Spearman’s correlation analysis demonstrated a statistically significant association between malocclusion severity and caries status (p = 0.001), with a correlation coefficient of r = 0.571, indicating a moderate positive relationship. Conclusion: The findings demonstrated a significant association between malocclusion severity and caries status among Banjar ethnic children aged 11–12 years at SDN Sungai Andai 4. Children with more severe malocclusion tended to exhibit higher caries status.Keywords: Banjar ethnic group, caries status, DMF-T, IOTN-DHC, malocclusion